Hypothyroidism in Adult Obese Patients - Hassan Shabbir,Nasira Shaheen,Muhammad Usman Rathore,Muhammad Qaiser Alam Khan (Journal of Rawalpindi Medical College, 2015)
Background: To determine the frequency of hypothyroidism in adult obese patients. Methods: In this cross sectional study 116 obese patients who reported in the outpatient department were included. Patients having body mass index (BMI) of more than 30 were considered obese. Patients suffering from chronic diseases such as tuberculosis, hypertension, ischemic heart disease, other endocrine disorders and patients under 18 years of age were not included. Registration at patient selection was followed by drawing of 4 - 5 ml of blood sample in the morning in plain serum bottle. The drawn samples were sent for serum TSH and serum free T4 levels . Patients having serum TSH level of more than 4.5 mIU/L and T4 levels of less than 8.0 pmol/L were considered hypothyroid. The patient’s height and weight were also measured using same machine for every patient for calculating BMI. The mean with standard deviation was calculated for age (years). Frequencies were calculated for hypothyroidism in obese patients and Chi Square test was applied to calculate the p value. Results: Out of 116 patients 6 (5.2%) of the obese cases were hypothyroid. The frequency of hypothyroid in our obese population is insignificant. Conclusion: There is no significant correlation between hypothyroid and obesity in our population.